Design and Applications of Continuous-Time Chaos Generators - Sánchez-López, Carlos; Muñoz-Pacheco, JesusManuel; Carbajal-Gómez, Victor Hugo; Trejo-Guerra, Rodolfo; Ramírez-Soto, Cristopher; Echeverria-Solis, Oscar S.; Tlelo-Cuautle, Esteban (IntechOpen, 2011)
None